Protective effect of ghrelin in oxidative stress-induced age-related macular degeneration in vitro and in vivo - Jie Bai; Yanqing Wang; Yanze Li; Yan Liu; Shan Wang (BMC, 2024)
Abstract Oxidative damage to human retinal pigment epithelial (RPE) cells is the main cause of age-related macular degeneration (AMD), in our previous work, we showed that ghrelin has an antioxidative effect on human lens epithelium (HLE) cells, however, the studies of using ghrelin in treating the degenerative diseases of the retina have rarely been reported. In this article, we assessed the effect of ghrelin on preventing oxidative stress induced by hydrogen peroxide (H2O2) in ARPE-19 cells and its mechanism. We observed that pretreatment with ghrelin protected ARPE-19 cells from H2O2-induced cell oxidative injuries and apoptosis responses. Furthermore, an oxidative stress-induced mouse model of AMD was established via injection of sodium iodate (NaIO3) to tail veins, and treatment with ghrelin preserved retinal function, and protected photoreceptors.